تأثيرُ المؤشرات المالية على أداء السهم دراسة تطبيقيةٌ في بورصةِ الأوراق الماليةِ المصرية خلال الفترة من 2008 إلى 2019 - سلطان , عادل عبد العزيز (Scientific Journal of University of Benghazi, 2021)
This study aims to measure the impact of financial indicators: book value per share, earnings per share, dividend per share, capital structure, current ratio, return on equity on the stock performance of companies listed on the Egyptian Stock Exchange, and determining which indicators are more explanatory. To achieve this, we analyzed a sample of seventeen companies listed on the stock exchange over a twelve-year period from 2008 to 2019, using statistical methods: Pearson's coefficient test, multiple regression analysis, simple regression analysis, and T-test. The findings of the research indicate the significance of the independent variables together on the dependent variable, and these variables explain (66.2%) of the variance in the dependent variable with a correlation coefficient (81.3%). When measuring each independent variable separately, it was proven that there was a statistically significant effect of the independent variables, with the exception of the Current Ratio.